Adsorbents Produced from Olive Mill Waste and Modified to Perform Phenolic Compound Removal - Rocha, Kleper de Oliveira [UNESP]; Brandão, Francisco; Mazierski, Pawel; Gomes, João; Martins, Rui C.; Domingues, Eva (MDPI, 2024)
Olive mill waste (olive pomace, OP, and olive stone, OS) was used in this work to produce adsorbents for the removal of five phenolic acids typically found in olive mill wastewater. OP and OS were subjected to different treatments (combined or not) that were chemically modified (NaOH) or physically modified by two different methods, incipient wetness impregnation (IWI) and hydrothermal deposition (HD), and even biochar production obtaining a total of 16 materials. The materials were characterized by different analytical techniques such as N2 absorption, scanning electron microscopy, infrared spectroscopy, and pH zero-potential charge. The mixture of five phenolic acids was used to evaluate in batch conditions the adsorption capacity of the prepared materials. OS chemically modified with IWI (OSM-IWI) and OS biochar with HD (BOS-HD) presented better adsorption capacity at 157.1 and 163.6 mg/g of phenolic acids, respectively, from a total of 200 mg/g. For some materials, the surface area cannot be correlated with adsorption capacity, unlike pHzpc, where high values fit better adsorption rates. The infrared spectroscopy profile indicates the presence of O-H and N-H functional groups and, the last one, red-shifted in the IWI preparation compared to the HD one. In addition to this, the prepared material from olive mill waste can be suitably used for the mixture of phenolic compounds.
Keywords: adsorption; biochar; chemical modification; olive mill waste; olive pomace; olive stone; phenolic acids